Financial Compliance in the European Union: A Cross‐National Assessment of Financial Correction Patterns and Causes in Cohesion Policy*. (7th December 2016) - Mendez, Carlos; Bachtler, John
Abstract: EU compliance scholarship has expanded rapidly over the last decade but has neglected the financial dimension of compliance in terms of Member States' conformity with EU financial rules on the regularity and legality of EU spending. This article makes the case for a multi‐dimensional approach to compliance research and provides the first cross‐national assessment of financial compliance in EU Cohesion policy, employing quantitative and qualitative methods. To account for cross‐national variations in the application of financial corrections for non‐compliant spending, several factors are explored, focusing on regional autonomy, administrative capacity and goodness‐of‐fit. The quantitative analysis finds strong support for the impact of administrative capacity on cross‐national compliance patterns and some evidence for the role of goodness‐of‐fit. Contrary to expectations, regional autonomy is not associated with compliance in this critical case of EU multi‐level governance. Qualitative analysis reinforces these findings while revealing additional factors of relevance.